2012
DOI: 10.3346/jkms.2012.27.11.1285
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Aditional Brief Counselling after Periodic Health Examination on Motivation for Health Behavior Change

Abstract: This study was to evaluate the effect of additional brief counseling by a primary care physician on lifestyle modification of examinees after a periodic health examination. 1,000 participants of the 2007 Korean national health screening program were asked to note any variation in their health behavior after participating in the screening program. The degree of comprehensive motivation for lifestyle modification was assessed in terms of stages of health behavior change. We calculated odds ratio of positive chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Research has focused on clients' readiness to change as a predictor of treatment outcomes. For example, some studies have indicated that individuals with increased readiness to change were more likely to reach treatment goals, such as lower body mass index and increased physical activity (Son et al, 2012;Jakubowski et al, 2012). Factors that have been linked with an increased readiness to change have included legal mandates (parole/probation), interpersonal relationships (significant others, parents, etc.…”
Section: Discussionmentioning
confidence: 97%
“…Research has focused on clients' readiness to change as a predictor of treatment outcomes. For example, some studies have indicated that individuals with increased readiness to change were more likely to reach treatment goals, such as lower body mass index and increased physical activity (Son et al, 2012;Jakubowski et al, 2012). Factors that have been linked with an increased readiness to change have included legal mandates (parole/probation), interpersonal relationships (significant others, parents, etc.…”
Section: Discussionmentioning
confidence: 97%
“…A study concerning a change in health behavior showed that lifestyle behaviors such as smoking, alcohol consumption, exercise and diet have improved in people who had periodic health examinations [25].…”
Section: Opinions About Screening Testsmentioning
confidence: 99%
“…ve arkadaşları, PSM'ye giden kişilerin sigara ve alkol tüketimini azaltma, düzenli egzersiz yapma ve sağlıklı beslenme gibi yaşam biçimlerindeki değişikliklerin birinci basamak hekimleri tarafından bu konularda motivasyonel görüşmeler yapılması sonucunda bu alışkanlıklarının olumlu yönde geliştiğini belirtmişlerdir. [14] Diğer taraftan da Kunnas ve arkadaşlarının yaptıkları 15 yıllık prospektif bir kohort çalışmasında hipertansiyonu ve diyabeti olan hastaların düzenli PSM'ye başvurmalarıyla beden kitle indekslerinde ve sistolik tansiyon ölçümlerinde artış görülmüş, yaşam tarzı değişikliklerinde önemli bir değişikliğe rastlanmamıştır. Tüm bu çalışmaların sonucunda da PSM'nin planlandığı gibi etkili olmadığı belirtilmiştir.…”
Section: Gereç Ve Yöntemunclassified